DEVELOPMENT OF INDICATORS OF POVERTY AND SOCIAL EXCLUSION IN THE YEARS 2009–2012 IN SLOVAKIA - Sedláková, Iveta; Sedláková, Andrea (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Ивета Седлакова, Андреа Седлакова. Развитие индикаторов бедности и социального исключения в годах 2009–2012 в Словакии. В статье отмечается, что распределение доходов на душу населения в Европейском Союзе очень неравномерное, отличается не только среди членов Союза, но и в отдельных географических регионах самимх стран непосредственно. Вместе с изменением размеров доходов, линия бедности перемещается и поэтому появляется угроза социального исключения для многих семей. В настоящей статье исследовано развитие индикаторов бедности в Словакии, начиная с 2009, когда евро было принято в качестве единого платежного средства, но в то же время экономика попала под влияние экономического кризиса, продолжавшегося и в 2012 году. Основой для сравнения данных были материалы ЕU SILC, рассмотренные и опубликованные Статистическим Отделом Словацкой Республики. Ключевые слова: бедность, черта бедности, экономический кризис, риск нищеты, социальные службы. Iveta Sedláková, Andrea Sedláková. Development of indicators of poverty and social exclusion in the years 2009–2012 in Slovakia. Distribution of income per capita in the EU is very uneven, varies not only among Member States but also geographically in regions of the countries themselves. Together with the amount of income, the poverty line is shifted and thus the threat of social exclusion for many households arises. This paper has examined the development of indicators of poverty in Slovakia since 2009, when the euro was adopted and at the same time the economy was influenced by the impact of the economic crisis until the year 2012. The basis for the comparison of data was the EU SILC survey published by the Statistical Office of the Slovak Republic. Key words: рoverty, Social еxclusion, risk of poverty, economic crisis. [